A Review of The Effects of Fruit Extracts Fortification on The Quality Characteristics and Antioxidant Activities of Yogurt - Lucyenne Angeline Giri Putra; Oki Krisbianto; Tatas Hardo Paningtingjati Brotosudarmo (Universitas Sebelas Maret (UNS), 2024)
Yogurt is one of the many variations of fermented milk food products that has a fairly high viscosity. Yogurt is classified as a functional food product because of its complete nutritional content and impact on the human digestive health system. The current condition of yogurt products is experiencing several developments, such as yogurt fortification with fruit extract to improve the quality of organoleptic yogurt. Not only does this addition affect the sensory quality, but it also decreases the pH value as well as increases the viscosity and the starter's viability. Moreover, fruit extract also increases yogurt’s functional characteristics through the enhancement of antioxidant content and activities. The changes and impact that are done to yogurt is influenced by several content which are found in the fruit extract that are added. Fruit extract’s compound contents affect and influence the microbial starter growth and metabolism activity, which is impactful towards changes in the quality characteristics of the resulting yogurt.